Fluid venting phenomena in the Eastern Mediterranean - Kearney, LM (2025)
Fluid venting poses clear risks to various industrial applications including carbon dioxide sequestration. To assess these risks, a detailed understanding of the conditions for fluid venting is required. While in-situ measurements of these conditions are scarce, recent observations of natural fluid vents in the Eastern Mediterranean provide robust constraints for the validation of predictive models. In this thesis, I develop a general theory of fluid venting and test it against these observations.